Episodic Nutrient Addition Affects Water Column Nutrient Processing Rates in River‐to‐Lake Transitional Zones. Issue 11 (28th October 2021) - Pearce, Nolan J. T.; Larson, James H.; Evans, Mary Anne; Frost, Paul C.; Xenopoulos, Marguerite A.
Abstract: Storm‐driven nutrient loading from tributaries can fuel eutrophication in nearshore and open water areas of lentic ecosystems. However, nutrient processing in river‐to‐lake transitional zones can substantially alter the amount and composition of nutrients transported to lakes from upstream surface waters. We measured the removal of nutrients and dissolved organic carbon (DOC) from the water column in the Fox rivermouth (Green Bay, Lake Michigan) to evaluate the response of rivermouth plankton to episodic nutrient enrichment. Light and dark water column incubations (8–12 hr) were conducted on four occasions from April through September to measure changes in dissolved nitrogen (N), phosphorus (P), and DOC concentrations in three locations along the Fox rivermouth. Two incubation experiments were conducted on consecutive days, (a) under ambient nutrient concentrations, and (b) under experimentally enriched N and P concentrations. Spatial and temporal variation was observed in nutrient uptake rates, but light incubations consistently had higher nutrient uptake rates than dark incubations. Nutrient enrichment increased total dissolved P and total dissolved N uptake and DOC release in light incubations, but only increased total dissolved P uptake in dark incubations. Moreover, nutrient uptake ratios (N:P) decreased from ambient to nutrient enriched conditions and indicated preferential P uptake by phytoplankton communities in light conditions. Our study substantiates that rivermouths can process nutrients bound for downstream ecosystems and demonstrates the potential of plankton communities to dynamically increase net uptake rates in response to episodic nutrient enrichment. Plain Language Summary: Nutrients washed into lakes from human activities (e.g., fertilizer application and livestock waste) can trigger the excessive growth of algae and harm nearshore ecosystems. Areas where large rivers enter lakes, also known as rivermouths, can capture these nutrients coming from the landscape and make them less available to algae in nearshore ecosystems. Yet, nutrients washed into rivermouths from rain events are only present for a short period of time and we do not know how much of these brief nutrient inputs can be removed through biological processes. Our study compared biological nutrient uptake rates in Fox rivermouth (Green Bay, Lake Michigan) under background conditions to those that mimicked a rapid increase in nutrients from a rain event. We found that biological nutrient uptake immediately increased when nutrients were added to the water column and changed the balance of the different types of nutrients captured by the rivermouth. Our study shows the potential for biological processes to capture additional nutrients when delivered to rivermouths in an episodic manner and at the same time transport more organic carbon downstream as a by‐product of increased biological activity. Key Points: Nutrient enrichment experiments were conducted to assess potential effects of climate‐induced storm events on rivermouth nutrient uptake Nutrient enrichment resulted in increased N and P uptake and dissolved organic carbon release in the water column Biological activity in light incubations had greater influence on water column nutrient dynamics than in dark incubations